Oxford handbook of pensions and retirement income - Clark, Gordon L.; Munnell, Alicia Haydock; Orszag, Michael (Oxford : Oxford University Press, 2006)
This handbook draws on research from a range of academic disciplines to reflect on the implications for provisions of pension and retirement income of demographic ageing. it reviews the latest research, policy related tools, analytical methods and techniques and major theoretical frameworks.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Pensions; Retirement income